ANALYSIS OF FACTORS AFFECTING OUTCOME OF ULTRASOUND‐GUIDED RADIOFREQUENCY HEAT ABLATION FOR TREATMENT OF PRIMARY HYPERPARATHYROIDISM IN DOGS. Issue 1 (24th November 2016) - Bucy, Daniel; Pollard, Rachel; Nelson, Richard
Abstract : Radiofrequency (RF) parathyroid ablation is a noninvasive treatment for hyperparathyroidism in dogs. There are no published data assessing factors associated with RF parathyroid ablation success or failure in order to guide patient selection and improve outcome. The purpose of this retrospective analytical study was to determine whether imaging findings, biochemical data, or concurrent diseases were associated with RF heat ablation treatment failure. For inclusion in the study, dogs must have had a clinical diagnosis of primary hyperparathyroidism, undergone cervical ultrasound and RF ablation of abnormal parathyroid tissue, and must have had at least 3 months of follow‐up information available following the date of ultrasound‐guided parathyroid ablation. Dogs were grouped based on those with recurrent or persistent hypercalcemia and those without recurrent or persistent hypercalcemia following therapy. Parathyroid nodule size, thyroid lobe size, nodule location, and presence of concurrent disease were recorded. Recurrence of hypercalcemia occurred in 9/32 dogs that had ablation of abnormal parathyroid tissue (28%) and one patient had persistent hypercalcemia (3%) following parathyroid ablation. Nodule width ( P = 0.036), height ( P = 0.028), and largest cross‐sectional area ( P = 0.023) were larger in dogs that had recurrent or persistent hypercalcemia following ablation. Hypothyroidism was more common in dogs with recurrent disease ( P = 0.044). Radiofrequency ablation was successful in 22/32 (69%) dogs. Larger parathyroid nodule size and/or concurrent hypothyroidism were associated with treatment failure in dogs that underwent ultrasound‐guided RF parathyroid nodule ablation.